Potential use of Red Palm Oil in Combating Vitamin A deficiency in India - Manorama, K (Indian Journal of Community Health, 2014)
Deficiency of vitamin A has long been recognized as a serious and preventable nutritional disease. Various intervention strategies have been implemented to combat the problem. Massive dosing of the vitamin has the advantage of immediate implementation but suffers from the disadvantage in that it applies to the isolated nutrient and requires repetitive administration. Natural food sources regularly included in diets offer a more viable long term solution. Red palm oil (RPO) can emerge as a viable alternative to other vitamin A rich foods, since it contains enormous amounts of natural carotenoids to the tune of around 700 PPM, the predominant ones being a and b carotene which have the highest biological potential for vitamin A conversion. Value addition of palm oil for edible purposes results in several nutritionally rich products like edible grade red palm oil (RPO), deacidified, deodourised RPOlein, isolated carotenoids and refined, bleached and deodourized palmolein oil RBD palmolein). RBD palmolein oil can serve as a replacement for any other commonly used edible oil, but has little additional advantage over other edible oils, stripped of its carotenoids. However, it’s naturally rich composition of tocopherols and tocotrienols, as well as the balanced fatty acid composition, makes it more superior to other edible oils used for dietary purposes. Addition of RBD palmolein to hydrogenated vegetable oil confers no advantage, and paradoxically, decreases it’s beneficial properties making it a more harmful vegetable oil from the cardiovascular health angle, because of conversion of fatty acids from the cis to trans type.